PENGARUH EKUITAS MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA VARIO 125 - Eigis Yani Pramularso (Jurakunman (Jurnal Akuntansi dan Manajemen), 2022)
The choice of products by buyers can occur because of the existing brand beliefs and the quality of the product. Purchasing decisions that are the target of the company can not be separated from brand equity and product quality so that it needs optimal attention and management by the company. The purpose of this study was to determine the effect of brand equity and product quality on the quality of purchasing a Honda Vario 125 motorcycle. The data collection method was carried out by distributing questionnaires to the user community which finally obtained a number of 40 people as respondents. This study uses multiple regression analysis as the data analysis with processing techniques using the SPSS 25 computer program. The results show that partially and jointly brand equity and product quality have a positive and significant influence on purchasing decisions.Keywords : brand equity; product quality; buying decision..